2019
DOI: 10.1002/ptr.6600
|View full text |Cite
|
Sign up to set email alerts
|

Bitter melon fruit extract has a hypoglycemic effect and reduces hepatic lipid accumulation in ob/ob mice

Abstract: Bitter melon (Momordica charantia L.) is a vegetable and has been used as traditional medicine. Recently, we reported that bitter melon fruit extracts and its ethyl acetate (EtOAc)-soluble fraction markedly suppressed the expression of proinflammatory genes, including the inducible nitric oxide synthase gene. However, it is unclear whether bitter melon exhibits antidiabetic effects. In this study, we showed that cucurbitacin B, a cucurbitane-type triterpenoid, was present in an EtOAc-soluble fraction and suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…We have previously shown that the exposure of methanol extract of bitter melon fruit for 8 h suppresses iNOS induction and NO production in IL-1β-treated hepatocytes, and that the hydrophobic fraction is responsible for the anti-inflammatory effect (14) . In addition, we found that 7 days of administration of the hydrophobic fraction to ob/ob mice reduces hepatic lipid accumulation and blood glucose levels (15) . Increases in insulin receptor expression in hepatocytes and serum insulin levels have also been observed (15) .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…We have previously shown that the exposure of methanol extract of bitter melon fruit for 8 h suppresses iNOS induction and NO production in IL-1β-treated hepatocytes, and that the hydrophobic fraction is responsible for the anti-inflammatory effect (14) . In addition, we found that 7 days of administration of the hydrophobic fraction to ob/ob mice reduces hepatic lipid accumulation and blood glucose levels (15) . Increases in insulin receptor expression in hepatocytes and serum insulin levels have also been observed (15) .…”
Section: Discussionmentioning
confidence: 73%
“…In addition, we found that 7 days of administration of the hydrophobic fraction to ob/ob mice reduces hepatic lipid accumulation and blood glucose levels (15) . Increases in insulin receptor expression in hepatocytes and serum insulin levels have also been observed (15) . These observations could be attributed to the anti-inflammatory effect of the hydrophobic fraction.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the IL-6 and TNF-α expression in epicardial adipose tissue were also reduced [28]. Another recent study by Dwijayanti and collegues found out that the expression of interleukin-1β mRNA and hepatic lipid accumulation in hepatocytes had been reduced in ob/ob mice type 2 diabetes mellitus model after 7 days of administration with ethyl acetate soluble fraction from MC fruit [18]. In addition, a previous study that involved MC-treated rat model showed that the levels of pro-inflammatory cytokines in the liver, muscle and epididymal fats were significantly down-regulated.…”
Section: Introductionmentioning
confidence: 90%
“…(MC) or bitter gourd belongs to Cucurbitaceae family. The fruit contains bitter, cucurbitane-type triterpenoids, including charantin, cucurbitacins and momordicins [18,19]. The seeds, fruit and leaves of MC had shown a wide range of pharmacological activities, and MC has been traditionally used for its therapeutic activities including anti-diabetic, anti-inflammatory, hypocholesterolemic, hypotriglyceridemic, antitumor, hypo-tensive, immunostimulant, anti-viral, antiinflammatory, anti-oxidant, anti-leukemic, antimicrobial, anthelmintic, anti-mutagenic, anti-ulcer, and insecticidal properties [20,21,22].…”
Section: Introductionmentioning
confidence: 99%